LEXICAL METAPHOR IN THE NOVEL AYAT-AYAT CINTA WRITTEN BY HABIBURRAHMAN EL SHIRAZY: SYSTEMIC FUNCTIONAL LINGUISTIC STUDY - Sudarko, Yayuk Nuriyani (Warmadewa University, 2017)
This research reports the result of transitivity investigation of lexical metaphor in the novel Ayat-Ayat Cinta and its relevance to language learning in SMA. The purpose of this study is to describe the transitivity process in the novel Ayat-Ayat Cinta; to describe the kinds of lexical metaphor that existed in the novel Ayat-Ayat Cinta; and to describe the relevance of research finding to language learning in high school. The approach used in this research is qualitative descriptive. Method of data collection is documen which covers the script documentation of the text in the novel Ayat-Ayat Cinta and recording technique. The data analysis was done by applying identification technique with the orientation Systematic Functional Linguistics (LFS). The results of data analysis were presented by using descriptive method comprising description the data anlyzed. The result showed that the presence of metaphor in transitivity in text of the novel Ayat-Ayat Cinta is very supportive for the research. It was found that the number of transitivity processes found is 247 clauses with the division into several processes. The percentage of material process is 19%, mental process 132%, relational process 8.50%, behavioral process 5.26%, verbal process 7.28%, and extential process is 6.47%. Based on the overall classification of process, the most dominant process realized in the novel is mental process (132%). (RELEVANCE OF RESEARCH FINDING TO LANGUAGE LEARNING AT SCHOOLS)